Temporal decision-making: insights from cognitive neuroscience - Luhmann, Christian C. (Frontiers in Behavioral Neuroscience, 2009)
Decisions frequently have consequences that play out over time and these temporal factors can exert strong influences on behavior. For example, decision-makers exhibit delay discounting, behaving as though immediately consumable goods are more valuable than those available only after some delay. With the use of functional magnetic resonance imaging, we are now beginning to characterize the physiological bases of such behavior in humans and to link work on this topic from neuroscience, psychology, and economics. Here we review recent neurocognitive investigations of temporal decision-making and outline the theoretical picture that is beginning to take shape. Taken as a whole, this body of work illustrates the progress made in understanding temporal choice behavior. However, we also note several questions that remain unresolved and areas where future work is needed.